A Study of Code Mixing on “Agak Laen” Podcast - Permata, Meiga; Yani, Juli; Goziyah, Goziyah (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
The language used for interaction can be characterized by symbols that are arbitrary in nature. Indonesia, with its vast linguistic diversity, often experiences phenomena like code mixing in daily conversations, which reflects the dynamic interplay between different languages. One setting where this can be observed is in podcasts, which are increasingly popular in Indonesia. In the podcast